The Characteristics of Bamboo Charcoal Derived from Bambusa vulgaris Schrad and Arundinaria gigantea (Walter) Muhl Growing in Different Types of Habitats - Ratri Yuli Lestari, M.Env.; Dwi Harsono; Nazarni Rahmi (Jurnal Riset Industri Hasil Hutan, 2018)
Altitude is one of the factors that affect the growth of bamboo. Bamboo species used in this study was Bambusa vulgaris and Arundinaria gigantea. The objectives of this study are to investigate the effect of altitude to the characteristics of bamboo charcoal harvested from three different altitudes (Lumpangi, Banjarbaru/Martapura, Marabahan). Parameters tested in this study were moisture content, ash content, volatile matter, fixed carbon and calorific value. The result showed that altitute significantly affected the characteristics of bamboo charcoal. Bamboo charcoal from Banjarbaru/Martapura had the best characteristics than the charcoal produced from other locations. The moisture content, ash content, volatile matter, fixed carbon and calorific value of B. vulgaris were 0.77 %; 3.49 %; 8.63 %; 87.11 % and 7,331.05 kal/g. The moisture content, ash content, volatile matter, fixed carbon and calorific value of A. gigantea were 0.19 %; 12.46 %; 4.48 %; 87.11 % and 6,640.69 kal/g, respectively.